Designing a sustainable structure for tennis competitions at national and regional level - Filipcic, A. (Coaching and Sport Science Review, 2024)
Tennis is a sport with many players and followers, as it has many positive effects on the health, well-being and social inclusion of participants. In the last ten years, tennis has undergone major changes in terms of organization, promotion and marketing. The tennis-like sports of padel and pickleball are becoming increasingly popular. All this brings many challenges and opportunities for global tennis organizations, regional and national federations and for individuals (club managers, coaches, parents and players). The aim of this article is to present some ideas on how tennis can be made more sustainable in order to create a more player-friendly development and ensure that more tennis players play and stay in the sport for longer.